Brexit: An Assessment of the Unprecedented Divorce Story and the Long Path to Ex-Membership - Gozde Kaya (European Scientific Journal, ESJ, 2020)
The UK which had been one of the major members of the EU, currently has been holding the status of an ‘ex-member’ following almost a four years of a rocky withdrawal process that took place for the first time ever in the EU history. This unprecedented withdrawal is likely to come up with severe negative outcomes particularly for the UK side in comparison to remaining in the Union. This study seeks to demonstrate the likely legal, political and economic ramifications of the British withdrawal by particularly concentrating on the highly critical and debated issues bargained during the withdrawal negotiations as well as to draw a detailed comparison of the outcomes of an exit under the framework of a withdrawal agreement and a no-deal scenario. Yet, the paper concludes that the second round of negotiations for determining on the terms of a future relationship might not be as less difficult than the first round examined in this study.